Desenvolvimento de um método para quantificação simultânea de sulfametoxazol e trimetoprima em ovos de galinha utilizando a cromatografia liquida de alta eficiência bidimensional - Paula, Fernando Campos Costa Rodrigues de (2007)
This work reports the investigation of a series of bovine serum albumin (BSA) restricted access media columns (RAM) for on-line egg samples deproteinization. High exclusion percentage of egg s proteins were obtained with the three RAM BSA columns prepared (C8, C18 and phenyl) using only water as eluent. However, an increase of pressure of the chromatographic system was observed at each injection, which made unfeasible the use of these columns for direct injection of the egg samples. To prolong the life-time of the RAM-BSA columns, acetonitrile was used as a protein precipitate agent. This clean-up procedure allowed the repetitive injection of 300 µL of whole egg samples. For the simultaneous quantification of sulfamethoxazole (SMX) and trimethoprim (TMP) in eggs samples, RAM-BSA columns, in different lengths (10 and 5 cm) sizes and different chromatographic conditions were thoroughly evaluated. A bidimensional higher performance liquid chromatography configuration having a RAM C18 BSA column in the first dimension, and a C18 analytical column in the second dimension were used for simultaneous quantification of these antibiotics. The developed method showed good selectivity, accuracy and precision with limits of quantification 80 ng/mL for both compounds. Thus, the validated method is reliable and sensitive for monitoring residues in whole eggs samples.